The physical development state of peasant children from the village Partyzany (southern Serbia, Yugoslavia) - Kaliszewska-Drozdowska, Maria Danuta (Anthropological Review, 1976)
On the ground of anthropometric examinations of 380 Yugoslavian country children aged 7-15, basic indices of their physical development are presented.